2003
DOI: 10.1046/j.1528-1157.2003.18802.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Intractable Partial Epilepsy Varies by Laterality of Focus and Surgery

Abstract: Summary:Purpose: Depression sometimes occurs after surgical treatment for medically intractable partial epilepsy. The risk of pre-and postsurgical depression may vary by laterality of seizure focus. We reviewed the pre-and postsurgical psychological assessments and clinical courses of patients to identify those at highest risk for postsurgical mood disorders.Methods: Depression status was assessed in a consecutive series of epilepsy patients before and 1 year after epilepsy surgery with the use of Scale 2 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 27 publications
0
45
2
1
Order By: Relevance
“…15) The present and previous findings have implicated TLE and presurgical psychiatric history as important risk factors for postoperative psychiatric problems. 1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…15) The present and previous findings have implicated TLE and presurgical psychiatric history as important risk factors for postoperative psychiatric problems. 1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…[1][2][3][4][5][6]9,11,[13][14][15]17,19) These problems have recently become a focus of interest, as intractable epilepsy is recognized as a chronic encephalopathy in which one seizure induces other seizures. 7) Therefore, we need to analyze the overall effects on the quality of life to demonstrate the benefits of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Quigg et al (2003) found that right-sided epilepsy patients with pre-surgical depression may be particularly susceptible to post-surgical depression, but Wrench et al (2004) have not confirmed a relationship between depression and temporal lobe epilepsy. Thirty-one subjects became depressed after 6 months, only two after 12 months from surgery.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to post-status epilepticus epilepsy, kindling is not accompanied by hippocampal sclerosis and spontaneous seizures. Eliminating spontaneous seizures as a variable permits this model to accommodate an important clinical feature of epilepsyassociated depression observed by Attarian et al [34] and Quigg et al [35]. Those authors found that the prevalence depression was independent of the degree of seizure control.…”
Section: Discussionmentioning
confidence: 99%